Cerebral metastases in lung cancer of non-small cells with egfr mutation: Metástasis cerebrales en cáncer de pulmón de células no pequeñas con mutación EGFR - Malpartida-Palomino, Robert (2019)
Lung cancer is one of the tumors that have the ability to metastasize in the brain and have the ability to penetrate the blood-brain barrier, the clinic is varied depending on the affected site, as well as the associated risks of convulsion. Therefore, the choice of treatment is complex, considering the primary, the number of metastases and the affected sites. Radiation therapy has long been the choice of patients who are not candidates for surgery, the presence of mutations have allowed to provide targeted therapies such as tyrosine kinase inhibitors that penetrate the blood-brain barrier and have been key to therapeutic management.   DOI 10.25176/RFMH.v19.n1.1798